Study of the differential microbiological quality of sheep milk relative to the standard plate counts - Jiménez L.; Oliete B.; Pérez-Guzman M.D.; Arias R. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Sheep milk production is a valuable sector for the European Mediterranean countries, and in the case of Castilla-La Mancha region (Spain), the production of sheep milk is linked with a high quality product. The hygienic quality of sheep milk is related to different groups of microorganisms, although farmers only have information about standard plate counts (SPC). The aim of this study was to evaluate the different bacterial counts (thermodurics, psychrotrophics, coliforms, Staphylococcus coagulase positive (SCP) and coagulase negative (SCN)) in relation with (SPC). A total of 283 bulk milk samples belonging to 26 herds distributed in Castilla-La Mancha region were collected during 2011. The mean values (log cfu/ml) of SPC, thermodurics, psychrotrophics, coliforms, Staphylococcus coagulase positive and coagulase negative were 5.49, 3.29, 4.89, 2.92, 2.68 and 4.10 respectively. In general, samples are distributed around low and intermediate intervals of microorganisms counts. It has been also confirmed a tight relationship between SPC and other microorganisms groups when counts are low. This relationship is more diffuse when high counts are considered. This fact could indicate the presence of other factors which only affect certain microorganisms groups. This work evidences the necessity of going through in the study of the global quality of ewes’ milk destined to cheese-making.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)